The Practice Level in Participatory Design Rationale: Studying Practicioner Moves and Choices - Selvin, Albert; Shum, Simon; Aakhus, Mark (Human Technology, 2010)
Most research in design rationale focuses on specific tools, methods, models, or artifacts. There has been relatively little attention to the practice level of design rationale work: the human experience of working with the tools and methods to create rationale artifacts. This paper explores a particular juncture of creativity and design rationale that is found in the special case of helping groups of people construct representations of rationale within live meetings. Such work poses challenges and requires skills different from those of individuals working alone. We describe the role of practitioners who perform caretaking and facilitative functions in collaborative or participatory design rationale sessions, and present a set of analytical tools aimed at making the practice level more visible. We locate the analysis in a theoretical framework aimed at understanding the experiential dimensions of such practice, including sensemaking, narrative, aesthetics, ethics, and improvisation.